Bis(μ-2,2′-biimidazole-κ(2) N (3):N (3′))bis[aquacopper(I)] sulfate - Zhang, Xiutang (International Union of Crystallography, 2009)
In the structure of the title compound, [Cu(2)(C(6)H(6)N(4))(2)(H(2)O)(2)]SO(4), the asymmetric unit contains half each of two 2,2′-diimidazole ligands, one Cu(+) cation, one water molecule and half of a sulfate anion (2 symmetry). The dinuclear complex is completed through a twofold rotation axis, leading to a twisted ten-membered ring molecule. The dihedral angle between the two symmetry-related 2,2′-diimidazole ligands is 23.6 (1)°. The copper centre is coordinated by two N atoms of two symmetry-related 2,2′-diimidazole ligands in an almost linear fashion. The water molecule exhibits a weak coordination to Cu(+) with a more remote distance of 2.591 (2) Å. The distance between the two copper centres is 2.5956 (6) Å. O—H⋯O and N—H⋯O hydrogen bonds between the complex cation, the water molecule and the sulfate anion lead to the formation of a three-dimensional network.